Involvement of Kallikrein-Related Peptidases in Nervous System Disorders - Mella, Cinthia; Figueroa, Carlos D.; Otth, Carola; Ehrenfeld, Pamela (Frontiers in Cellular Neuroscience, 2020)
Kallikrein-related peptidases (KLKs) are a family of serine proteases that when dysregulated may contribute to neuroinflammation and neurodegeneration. In the present review article, we describe what is known about their physiological and pathological roles with an emphasis on KLK6 and KLK8, two KLKs that are highly expressed in the adult central nervous system (CNS). Altered expression and activity of KLK6 have been linked to brain physiology and the development of multiple sclerosis. On the other hand, altered levels of KLK6 in the brain and serum of people affected by Alzheimer’s disease and Parkinson’s disease have been documented, pointing out to its function in amyloid metabolism and development of synucleinopathies. People who have structural genetic variants of KLK8 can suffer mental illnesses such as intellectual and learning disabilities, seizures, and autism. Increased expression of KLK8 has also been implicated in schizophrenia, bipolar disorder, and depression. Also, we discuss the possible link that exists between KLKs activity and certain viral infections that can affect the nervous system. Although little is known about the exact mechanisms that mediate KLKs function and their participation in neuroinflammatory and neurodegenerative disorders will open a new field to develop novel therapies to modulate their levels and/or activity and their harmful effects on the CNS.